Treatment of oligometastatic breast cancer: The role of patient selection - Riccardo Ray Colciago; Maria Carmen De Santis; Carlotta Giandini; Maria Grazia Carnevale; Serena Di Cosimo (Breast)
Up to 90 % of death from solid tumors are caused by metastases. By 2040, breast cancer (BC) is predicted to increase to over 3 million new cases. Additionally, with the personalization and intensification of BC follow-up, many patients will relapse with oligometastatic disease (OMD). Over the past decades, advances in treatment planning, image guidance, target position reproducibility, and online tracking, along with a compelling radiobiological rationale, have led to the implementation of Stereotactic Body Radiation Therapy (SBRT). This has become a valid ablative treatment option for OMD patients.However, there are still concerns about which patients benefit the most from ablative treatment. In this review, we will analyze the literature regarding SBRT for OMD in BC patients. We aim to present the current data on its effectiveness and define the optimal tailored scenarios for SBRT outcomes.